127 Early Versus Late CMR in Troponin-Positive Chest Pain with Unobstructed Coronaries. (6th June 2015) - Singhal, Priyanka; Dastidar, Amardeep Ghosh; Rodrigues, Jonathan C; Ahmed, Nauman; Palazzuoli, Alberto; Townsend, Mandie; Nightingale, Angus; Johnson, Tom; Strange, Julian; Baumbach, Andreas; Bucciarelli-Ducci, Chiara
Abstract : Background: Acute coronary syndrome (ACS) is one of the leading causes of morbidity and mortality. Up to 15% of ACS patients are left with a diagnostic dilemma when no significant coronary obstruction is identified. In these patients, CMR can identify different underlying diagnoses including: myocarditis, myocardial infarction (MI) with spontaneous recanalisation/embolus or Tako-Tsubo cardiomyopathy. However, there are discrepancies in the literature on the diagnostic pick-up rate by CMR and patients are not consistently scanned in the same time window. Aim: To evaluate the diagnostic role of performing CMR "early" (< 2 weeks from presentation) versus "late" (>2 weeks from presentation) in patients with troponin positive ACS and unobstructed coronaries. Methods: In this retrospective observational study, performed at a large cardiothoracic tertiary centre in the South-West of England, data were collected on consecutive patients with troponin positive ACS and unobstructed coronaries, referred for a CMR (September 2011 to July 2014). CMR was performed on a 1.5T scanner (Avanto, Siemens) using a comprehensive protocol that included long- and short-axis cines, T2 weighted STIR and early and late gadolinium enhancement. Each scan was reported by a consultant with >10 yrs CMR experience. Results: 204 consecutive patients (mean age 55 yrs) were included in the analysis (51% males). The median time interval between presentation and CMR was 20 days (range 1–150 days). An "early" CMR was performed in 96 patients (median 6 days and range 1–14 days) and 108 patients underwent a "late" CMR scan (median 41 days and range 15–150 days). Overall, CMR identified a diagnosis in 70% of patients, whilst the remaining 30% of patients were classified as normal/unknown diagnosis. An "early" CMR scan significantly improved the diagnostic pick-up rate compared to a "late" CMR scan: 82% vs 54% respectively (p < 0.0001). Myocarditis was the most common diagnosis in "early" CMR (34%) whereas reperfused MI in "late" CMR (26%). Conclusion: The diagnostic role of CMR is significantly improved when performed within 2 weeks of acute presentation of troponin positive ACS with unobstructed coronaries. "Early" CMR established a final diagnosis in 82% of a large cohort of patients. In patients with ACS and unobstructed coronary arteries, CMR should be offered within a specified time window, ideally <2 weeks from presentation, in order to increase its diagnostic role and guide appropriate patient management.